2021
DOI: 10.1590/pboci.2021.165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bracket Position Accuracy with Different CAD/CAM Indirect Bonding Systems

Abstract: Objective: To evaluate the accuracy of three different digital bracket positioning systems, comparing vertical, mesiodistal and buccolingual accuracy. Material and Methods: The same case was sent to Orapix, Insignia, and Orthocad systems and the brackets were bonded to the malocclusion models. Damon 3 MX brackets were used with all systems and the brackets were bonded to the models with the same bonding protocol and materials. The comparison of the position of each single bracket was made with digital photogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…For the Insignia™ jigs, the B-L translation in most brackets was more buccally positioned in most teeth (92.92%). This finding agrees with the studies reported by Paolo et al [ 42 ] and Grunheid et al [ 37 ]; they found that most of the brackets are placed more buccally from the buccolingual aspect when compared three different CAD/CAM indirect bonding systems in the former study, while in the second study was used the vinyl polysiloxane trays that have some flexibility, which may allow the adhesive to push the brackets a little bit more buccally. At the same time, the frequency of angular errors was in the torque for most brackets with more buccal crown torque (73.33%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the Insignia™ jigs, the B-L translation in most brackets was more buccally positioned in most teeth (92.92%). This finding agrees with the studies reported by Paolo et al [ 42 ] and Grunheid et al [ 37 ]; they found that most of the brackets are placed more buccally from the buccolingual aspect when compared three different CAD/CAM indirect bonding systems in the former study, while in the second study was used the vinyl polysiloxane trays that have some flexibility, which may allow the adhesive to push the brackets a little bit more buccally. At the same time, the frequency of angular errors was in the torque for most brackets with more buccal crown torque (73.33%).…”
Section: Discussionsupporting
confidence: 92%
“…This error can be attributed to the consistency of the bonding material under the customized metal bracket base [ 43 , 44 ]. In addition, the jig could not cover the undercut of a bracket, and the elasticity of the separator material that would be used to make a free gap between the transfer jig and the bracket may have an effect [ 42 ]. So, these properties of the jig material could influence the accuracy of the bracket position.…”
Section: Discussionmentioning
confidence: 99%